Decision-to-delivery interval in emergency cesarean delivery in tertiary care hospital in Thailand - Khemanat Khemworapong (2019)
© 2018 Korean Society of Obstetrics and Gynecology. Objective To determine the decision-to-delivery interval (DDI) in emergency cesarean delivery and associated factors. Methods A total of 431 pregnant women who were indicated for emergency cesarean delivery were included. Clinical information and timing of process after decision until delivery and pregnancy outcomes were evaluated. Results Mean age was 30 years, and 59.4% were nulliparous. Mean gestational age at delivery was 37.9 weeks. The decision was made during normal office hour in 33.2%. Median decision-to-operating room interval, decision-to-incision interval, and DDIs were 45, 70, and 82 minutes, respectively. Only 3.5% of patients had DDI = 30 minutes, while 52.0% had DDI > 75 minutes. During after office hours, every time interval was significantly shorter and 4.9% had DDI = 30 minutes compared to 0.7% in normal office hours (P = 0.001). Compared to other indications, time intervals were significantly shorter in those with non-reassuring fetal heart rate (FHR), and DDI =3 0 minutes was achieved in 18.8% vs. 0.8% (P < 0.001). Shortest DDI was observed among those with non-reassuring FHR during after office hours. Neonatal outcomes were comparable between different DDIs. Conclusion Only 3.5% of emergency cesarean delivery had a DDI = 30 minutes (median 82 minutes). Significant shorter time intervals were observed in those with non-reassuring FHR during after office hours.